How is depression experienced around the world? A systematic review of qualitative literature. (June 2017) - Haroz, E.E.; Ritchey, M.; Bass, J.K.; Kohrt, B.A.; Augustinavicius, J.; Michalopoulos, L.; Burkey, M.D.; Bolton, P.
Abstract: To date global research on depression has used assessment tools based on research and clinical experience drawn from Western populations (i.e., in North American, European and Australian). There may be features of depression in non-Western populations which are not captured in current diagnostic criteria or measurement tools, as well as criteria for depression that are not relevant in other regions. We investigated this possibility through a systematic review of qualitative studies of depression worldwide. Nine online databases were searched for records that used qualitative methods to study depression. Initial searches were conducted between August 2012 and December 2012; an updated search was repeated in June of 2015 to include relevant literature published between December 30, 2012 and May 30, 2015. No date limits were set for inclusion of articles. A total of 16, 130 records were identified and 138 met full inclusion criteria. Included studies were published between 1976 and 2015. These 138 studies represented data on 170 different study populations (some reported on multiple samples) and 77 different nationalities/ethnicities. Variation in results by geographical region, gender, and study context were examined to determine the consistency of descriptions across populations. Fisher's exact tests were used to compare frequencies of features across region, gender and context. Seven of the 15 features with the highest relative frequency form part of the DSM-5 diagnosis of Major Depressive Disorder (MDD). However, many of the other features with relatively high frequencies across the studies are associated features in the DSM, but are not prioritized as diagnostic criteria and therefore not included in standard instruments. The DSM-5 diagnostic criteria of problems with concentration and psychomotor agitation or slowing were infrequently mentioned. This research suggests that the DSM model and standard instruments currently based on the DSM may not adequately reflect the experience of depression at the worldwide or regional levels. Highlights: Reviews qualitative literature to identify features of depression worldwide. Emphasizes importance of qualitative data to enhance understanding of depression. Investigates potential biases in Western instruments that measure depression. Argues that Western diagnostic criteria do not represent depression globally.